Profile of partnerships between the Instituto Nacional de Tecnologia and innovation players: a study of scientific collaborations - Ricardo Ferreira Vieira de Castro; Andreia Cristina Galina; Larissa Campos de Medeiros; Suzana Borschiver (Transinformação)
Abstract This study analyzes the collaborative relationship based on the scientific production of a Brazilian public technological research institute, the National Institute of Technology, using the Scopus and Web of Science databases. It is a scientometric study where the analyses were conducted based on collaborations with organizations with which National Institute of Technology published scientific articles, involving different actors in innovation, categorized as Scientific, Technological, and Innovation institutions, companies, and government, following the “Triple Helix” innovation model. Out of the 923 retrieved documents, 654 were articles, with 543 published in collaboration and 111 solely authored by National Institute of Technology. The research identified that the majority of collaborations occurred with scientific institutions classified as educational. Interactions with state-run and private companies from various industry sectors were also identified, and in a smaller number with government institutions. The geographical aspect was also explored, mapping partnerships by region and federal unit. The Southeast region had the highest number of collaborations, with a significant presence in the state of Rio de Janeiro and São Paulo.